2002
DOI: 10.1083/jcb.200106008
|View full text |Cite
|
Sign up to set email alerts
|

Serum response factor is crucial for actin cytoskeletal organization and focal adhesion assembly in embryonic stem cells

Abstract: The activity of serum response factor (SRF), an essential transcription factor in mouse gastrulation, is regulated by changes in actin dynamics. Using Srf(−/−) embryonic stem (ES) cells, we demonstrate that SRF deficiency causes impairments in ES cell spreading, adhesion, and migration. These defects correlate with defective formation of cytoskeletal structures, namely actin stress fibers and focal adhesion (FA) plaques. The FA proteins FA kinase (FAK), β1-integrin, talin, zyxin, and vinculin were downregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
166
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(177 citation statements)
references
References 78 publications
9
166
1
1
Order By: Relevance
“…BARX2 might promote serum-dependent migration by any of these mechanisms. For example, BARX2 influences the cytoskeleton (Meech et al, 2003) and interacts with the serum response factor (SRF) (Herring et al, 2001), which controls actin-directed cell spreading (Schratt et al, 2002). BARX2 also increases transcription of MMP9, which is known to promote invasion of cancer cells via matrix degradation (Vu et al, 1998;Balduyck et al, 2000;Zhao et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…BARX2 might promote serum-dependent migration by any of these mechanisms. For example, BARX2 influences the cytoskeleton (Meech et al, 2003) and interacts with the serum response factor (SRF) (Herring et al, 2001), which controls actin-directed cell spreading (Schratt et al, 2002). BARX2 also increases transcription of MMP9, which is known to promote invasion of cancer cells via matrix degradation (Vu et al, 1998;Balduyck et al, 2000;Zhao et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in embryonic stem cells null for SRF showed defects in cell migration, presumably as a result of a disrupted cytoskeleton (6). Interestingly, flies and social amoeba null for SRF also display defects in cell migration that are thought to be a result of an altered cytoskeleton (5,28).…”
Section: Srf-dependent Gene Expression Is Compromised In Mutant Embryosmentioning
confidence: 99%
“…One or more CArG boxes (consensus ϭ CCW 6 GG) are found within the proximal promoter or first intron of Ͼ60 SRF-dependent genes, half of which are restricted to cardiac, skeletal, and smooth muscle (SM) cells (SMCs) (1,2). Genetic inactivation of SRF in amoeba (3), worm (4), fly (5), and mouse embryonic stem cells (6) has confirmed a critical role for SRF in normal cytoskeletal architecture, cell adhesion, cell migration, and͞or animal movement. These results are consistent with data in transgenic reporter mice showing the functional importance of CArG elements in muscle promoter activity (2,7).…”
mentioning
confidence: 99%
“…There is growing evidence that the integrity of the nucleus (Lammerding et al, 2004;Lammerding et al, 2005;Hale et al, 2008) and mechanotransduction signaling (Lammerding et al, 2005;Emerson et al, 2009) might be impaired in the diseases linked to mutations in A-type lamins and lamin-associated proteins. Recent major findings from the Lammerding group show that cells and cardiac tissue from A-type lamin mutant mice have impaired nuclear translocation and downstream signaling of megakaryoblastic leukemia 1 protein (MKL1, also known as MRTF-A and MAL) (Ho et al, 2013), a transcription factor which regulates, through serum response factor (SRF), the expression of signaling molecules, transcription factors and numerous cytoskeletal components, including actin genes, nonmuscle myosins and vinculin (Schratt et al, 2002;Cen et al, 2003;Miralles et al, 2003). Deregulation of MKL1-SRF signaling is attributed to changes in actin dynamics in lamin A/C mutant mouse embryonic fibroblasts (MEFs) (Ho et al, 2013).…”
Section: Introductionmentioning
confidence: 99%